Analisis Framing dan Etika Penyiaran terhadap Representasi Pesantren dalam Tayangan Xpose Uncensored Trans7 - Nisrina Nabibah Sunarto; Laili Zulfa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the construction of reality and violations of broadcasting ethics in the Xpose Uncensored Trans7 program in 2025 which displays a negative image of pesantren and kiai. Using a descriptive qualitative approach with the framing analysis of Pan and Kosicki's model, this study reveals the existence of tendentious narrative and visual manipulation, thus giving the impression of harassment of religious symbols. The broadcasts are considered to violate the principles of balance and social responsibility as stipulated in the Broadcasting Code of Conduct and Broadcast Program Standards (P3SPS). The public reaction that emerged through the hashtag #BoikotTRANS7 reflects the increasing public awareness of the importance of ethics in broadcasting practices. This phenomenon shows that the media not only functions as a conveyor of information, but also has a moral responsibility in shaping public opinion in a fair and balanced manner. This study emphasizes the urgency of increasing media literacy and ethical sensitivity in the production of broadcast content, especially those related to the representation of religious groups. Thus, the results of this study are expected to be a reference for broadcasting institutions, media regulators, and the public in encouraging more ethical and responsible broadcasting practices in the digital era.